Novel hexanoyl chitosan/ENR25 blend polymer electrolytes for application in electrical double layer capacitor (EDLC) / Nur Asheila Nadirah Jamaluddin - Jamaluddin, Nur Asheila Nadirah (2018)
Hexanoyl chitosan soluble in THF is prepared by acyl modification of chitosan. Epoxidized natural rubber (ENR25) (25 mol%) is chosen to blend with hexanoyl chitosan. Elastic property of hexanoyl chitosan was enhanced with the incorporation of ENR25. DSV and DSC studies revealed immiscibility of hexanoyl chitosan and ENR25.